Bovine Pre-adipocyte Adipogenesis Is Regulated by bta-miR-150 Through mTOR Signaling - Chen, Xingyi; Raza, Sayed Haidar Abbas; Ma, Xinhao; Wang, Jiangfang; Wang, Xiaohui; Liang, Chengcheng; Yang, Xinran; Mei, Chugang; Suhail, Syed Muhammad; Zan, Linsen (Frontiers in Genetics, 2021)
Micro RNA (miR) is recognised for their important roles in biological processes, particularly in regulatory componentisation. Among these, miR-150 has been the focus of intense scrutiny, mostly due to its role in malignant tumours. A comparison between steer and bull adipose tissues identified bta-miR-150 as one of the nine downregulated miRNAs, although its function remains unknown (GEO:GSE75063). The present study aimed to further characterise the role of bta-miR-150 in cattle. The bta-miR-150 has a negative regulatory effect on the differentiation of bovine adipocytes and promotes proliferation. Overexpression of bta-miR-150 can promote mRNA and protein expression of the marker genes, CDK1, CDK2, and PCNA, increase the number of EdU-stained cells, promote the proliferation of adipocytes, inhibit adipocyte differentiation, and reduce lipid droplet formation. The results of RNA-seq and WGCNA analyses showed that the mammalian target of rapamycin signalling pathway, which plays a major regulatory role, is dysregulated by the overexpression and inhibition of miR-150. We found that the target gene of bta-miR-150 is AKT1, and that bta-miR-150 affects AKT1 phosphorylation levels. These results showed that bta-miR-150 plays a role in adipogenic differentiation and might therefore have applications in the beef industry.